Estimativa do custo do abastecimento de água baseado no consumo de energia: estudo de caso na Universidade Federal da Paraíba - Vieira, Anderson Karlo Fernandes (2019)
For many years, water was considered an infinite natural resource, but the high consumption added to the waste, has alerted authorities and population about the importance of saving. In the Brazilian legal system, it is considered a public property and a limited naturalresource, endowed with economic value. In this context, environmental sustainability is related to the adequate and rational use of natural resources, taking into account their limited capacity. This work investigates the consumption of groundwater collected through artesian wells that are used to supply the UFPB, Campus I. The determination of the consumption is necessary, since there are no measurement devices that allow to know the amount of water abstracted of wells. Thus, this volume was determined through inferences between the consumption of electric energy related to the operation of the engines that stress the fluid, measured by means of appropriate equipment during a period of 30 days, and the value of the cubic meter of water of the local dealer. It was verified that the consumption of energy in this period was 3,885.50 kWh, equivalent to the volume of water added of 12,781.50 m³. During the process of analysis of the results, the UFCG supply system was used as a parameter, which has an annual cost of supply of R $ 23.67 / enrolled student, while the UFPB has a R $ 184.81 / enrolled student. From the knowledge of the volume of water consumed, it is possible to propose management measures to combat, control and operationalize the system in order to avoid losses of this precious liquid, as well as to promote the sustainable use of available water resources.